Recent advances on hydrogen generation based on inorganic metal oxide nano-catalyst using water electrolysis approach - Muhammad Naeem, Ayub; Muhammad Fazle, Rabbee; Umer, Shahzad; Mohsin, Saeed; Saad M., Al-Baqami; Khalid A., Alzahrani; Md. Reazuddin, Repon; Md. Rezaur, Rahman; Mohammad Mizanur, Rahman Khan; Mohammed M., Rahman (De Gruyter, 2024)
Today world is looking for a cheap, environment friendly and efficient substitute of fossil fuel. Because due to large consumption of the fossil fuels on daily basis in whole world, emission of hazardous gases have produced lethal effects on human being. In this scenario hydrogen energy has emerged in form of clean, renewable and more efficient energy. Now the key challenge is that efficient production of the green hydrogen at commercial scale to meet demand of hydrogen. The electrolysis of water is the best pathway to achieve efficient hydrogen production. For this purpose the synthesis and improvement of low cast, active as well as stable catalysts or electrolysis is prerequisite for hydrogen production by electro-catalytic method for splitting of water. Main focus of this review is that, how we can perform the electrolysis of water by various techniques using novel methods especially electro-catalysts in term of activity, efficiency, large surface area, porosity, and stability. This will be performed by the method of two-half cell reaction one is the Hydrogen Evolution Reaction (HER) other one Oxygen Evolution Reaction (OER), where reaction proceeded in both medium acidic as well as alkaline phases. Particular attention is given to produce green clean hydrogen production from usable water and its physical and chemical storages for further uses for the support of human sustainability. Basically the recent strategy is to prepare, design and development of nanoscale materials/composite with non-noble metals and with also nanostructured with noble-metals will be discussed in this approach. The increased efficiency and utility have been the focal points of the use of diverse materials from different classes. To increase the electrocatalytic efficiency in OER and HER, we will discuss about new analyses methods and insights into studying the chemical compositions, shapes, surface area, porosity, and synergy of catalysts and the active sites of nanostructured electro-catalysts. This review will further provide the picture of current state of developments as well as recent progress for mechanized efficient production of clean hydrogen (i.e., HER) from water by electrocatalytic method using various nanoscale materials in a broad scale.